A Goal Programming Model for Fairly Scheduling Medicine Residents - Elomri, Adel; Elthlatiny, Sara; Sidi Mohamed, Zainab (International Journal of Supply Chain Management, 2015)
In this study we develop a goal programming model for scheduling the shifts of the residents in a Qatari hospital. The residents are assigned for on-call shifts during their training (called first resident), as well as working during the regular day shifts (called helper). Residents’ schedules must address several considerations like work rules and hospital coverage requirements of two different departments: Oncology and Hematology as well as fairness of the workload distribution. The problem has been formulated using goal programming and solved using CPLEX. We were able to solve problems of realistic size to optimality in a few seconds.